The Effectiveness of an Intervention Programme on Working Memory Plus Arithmetic Knowledge (WM+A)Title - Tsai, Kuan-Chun; Nunes, Terezinha; Barros, Rossana (Journal of China-ASEAN Studies, 2022)
The aim of the study is to examine the effectiveness of an intervention programme (WM+A) which is designed to improve children’s maths attainment. The intervention programme consists of two parts: working memory intervention and arithmetic knowledge intervention. Three research questions are asked: (1) What is the effect of WM+A intervention on children’s numeracy skills? (2) What is the effect of WM+A intervention on children’s working memory? (3) What is the effect of WM+A intervention on children’s attention and behaviour in class? The investigation will be carried out at international schools in Thailand, which follow the National Curriculum in England and use English as a medium of instruction for teaching and learning. Pre-tests will be given to assess children’s numeracy skills, working memory, attention and behaviour in class, followed by intervention session for 10 weeks. Children will receive 5 weeks of working memory intervention, followed by 5 weeks of arithmetic knowledge intervention. During the intervention session, half of the time will be one-to-one teacher led activities, and the other half will be computer games that reinforce the strategy and concepts which have been learned in the teacher led activities. Post-tests will then be conducted to measure the outcomes and evaluate the effectiveness of the WM+A intervention programme. It is expected that the current study will contribute both to the theory of children’s maths attainment and on the practice of maths education.